1994
DOI: 10.1590/s0034-89101994000300004
|View full text |Cite
|
Sign up to set email alerts
|

Padrão alimentar de idosos de diferentes estratos socioeconômicos residentes em localidade urbana da região sudeste, Brasil

Abstract: NAJAS, M.S. et al. Padrão alimentar de idosos de diferentes estratos socioeconômicos residentes em localidade urbana da região sudeste, Brasil. Rev. Saúde Pública, 28:187 -91,1994. Foram estudados 283 idosos do sexo masculino e feminino pertencentes ao projeto multicêntrico "Identificação de Necessidades dos Idosos Residentes em Zona Urbana do Município de São Paulo", estratificados por nível socioeconômico em três regiões do Município de São Paulo, SP -Brasil. Utilizou-se o método de freqüência de alimentos p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
26

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 8 publications
1
3
0
26
Order By: Relevance
“…A study carried out with data from Pesquisa de Orçamento Familiar (POF -Family Budget Research) of Fundação Instituto de Pesquisas Econômicas of Universidade de São Paulo in 1998/1999 about the acquisitions of food and beverages for family consumption during one month showed that the participation of fruits and vegetables in the overall amount 10 Low level of schooling can also influence consumption and the small variability of fruits and vegetables, due to the adoption of inadequate dietary habits and due to the higher frequency of agerelated problems (locomotion difficulties, chewing and swallowing problems, diseases such as depression and dementia). 2,4,14,16 The effect of low level of schooling could explain, at least in part, the small variability in fruit intake observed here. We found that among the least consumed fruits were those whose cost is high in the state of São Paulo, b like strawberry, fig, peach and of calories increases as the family income increases and the price of the fruits and vegetables decreases.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A study carried out with data from Pesquisa de Orçamento Familiar (POF -Family Budget Research) of Fundação Instituto de Pesquisas Econômicas of Universidade de São Paulo in 1998/1999 about the acquisitions of food and beverages for family consumption during one month showed that the participation of fruits and vegetables in the overall amount 10 Low level of schooling can also influence consumption and the small variability of fruits and vegetables, due to the adoption of inadequate dietary habits and due to the higher frequency of agerelated problems (locomotion difficulties, chewing and swallowing problems, diseases such as depression and dementia). 2,4,14,16 The effect of low level of schooling could explain, at least in part, the small variability in fruit intake observed here. We found that among the least consumed fruits were those whose cost is high in the state of São Paulo, b like strawberry, fig, peach and of calories increases as the family income increases and the price of the fruits and vegetables decreases.…”
Section: Discussionmentioning
confidence: 69%
“…2,6,9,10,14 Jaime & Monteiro 9 (2005) investigated the fruit and vegetable intake in a national probabilistic sample composed of 5,000 individuals, including elderly people. These authors used short questions to obtain information on the intake of these food items and their results were similar to the ones of the present study, with 20.6% of the women meeting the WHO recommendations, but only 14.8% of the men.…”
Section: Discussionmentioning
confidence: 99%
“…Assim surgem quadros de baixo peso e desnutrição ou de sobrepeso e obesidade, frequentes no idoso, com alterações importantes nos parâmetros lipêmicos e glicêmicos (GARIBALLA; SINCLAIR, 1998). Em estudo realizado com diferentes grupos sócio-econômicos, verificou-se que os idosos apresentaram o mesmo padrão alimentar que outros grupos populacionais no tocante aos alimentos energéticos, porém, diferiram quanto aos protéicos e reguladores, os quais ingeriam em menor quantidade (NAJAS et al, 1994).…”
Section: Relação Do Sistema Imunitário E O Estado Nutricionalunclassified
“…Em um outro estudo que pretendeu identificar as principais diferenças entre o padrão alimentar de idosos paulistanos de classes sociais distintas, Najas et al (1994) A adoção de dietas balanceadas e a redução de sal e açúcar, por exemplo, são consideradas alterações substanciais em práticas alimentares de pessoas idosas, principalmente entre indivíduos que passaram parte significativa de suas vidas consumindo gordura e grandes quantidades de carboidratos para realizarem trabalhos que lhes demandaram grande esforço físico. Assim, em alguns segmentos de idosos, pode-se encontrar resistência em adquirir novos hábitos, devido à valorização da cultura alimentar vivenciada na família e à consolidação de práticas estabelecidas, valorizadas simbolicamente por esses (LAUREATI et al, 2006).…”
Section: Troduçãounclassified